Diseño e implantación de un reservorio de agua y red de distribución de riego en la finca la neblina - San Vicente - Alóag - Pichincha - Ramírez Gamboa, Roberto Alonso (2014)
Water is the fundament part for agriculture therefore it is essential the conservation of the flora and fauna of the sources where the vital liquid comes and thus use irrigation methods that allow the optimization and adjustment of the same on the scientific knowledge of the design irrigation systems. Thus achieving efficiency and quality for the provision of irrigation. For the present investigation called Design and implementation of a water reservoir and distribution network on irrigation in the neblina farm located in the San Vicente neighborhood Alóag parrish, Mejía canton in the province of Pichincha. Year 2012….